The role of the neural crest in the normal and abnormal heart development - Mashtalir M.A.; Tverdokhleb I.V.; Kozlov V.A. (Морфологія, 2007)
The data about participation of the neural crest in the normal and abnormal cardiogenesis are summarized in the review. The main morphological phenomena which accompany the interaction of the neural crest cells and embryonic heart are the migration of the dense mesenchyme originated from neural crest from pharyngeal arches to the trunk of heart as well as apoptotic processes. After chemical teratogens treatment such as retinoic acid and ethyl alcohol the distant relationship between neural crest and heart and also the migration of neural crest cells to the heart were changed. The decrease of inten-sity of the apoptotic processes in the heart, the delay of reduction of the conotruncal and atrioventricular myocardium and lesion of mesenchyme structures were determined morphologically. The ethanol and retinoic acid treatment cause also the abnormalities in the interventricular foramen closure, in the development of conductive system, and heart valves. We suggest that these abnormalities are mediated by the neural crest cells.